Use of ebastine a mast cell blocker for treatment of oligozoospermia - Deeba, Farzana; Ishrat, Shakeela; Banu, Jesmine; Anawary, Shaheen Ara; Begum, Nurjahan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Global infertility prevalence rates are difficult to determine, due to the presence of both male and female factors which complicate any estimate which may only address the woman and an outcome of a pregnancy diagnosis or live birth. Although overall male fertility does not appear to have declined, there is evidence for decline in sperm quality. Sperm count below 15×106 sperm/ml is called oligozoospermia. The aim of this study was to evaluate the efficacy of ebastine on sperm count of oligospermic infertile men. Methods: This was a longitudinal clinical trial study and was conducted in the infertility unit outdoor, Department of Obstetrics and Gynecology, Bangabandhu Sheikh Mujib Medical University, Dhaka. Bangladesh during the period from January 2015 to December 2015. This study was conducted among the male patients and followed purposive sampling technique. Finally, 334 cases were enrolled in this study. Results: From the total 334 patients in group I, mean sperm count was 10.32±2.71 million/ml in pretreatment and 18.87±9.56 million/ml in post treatment. The difference was statistically significant (p<0.05). In group II, mean sperm count was 10.19±1.75 million/ml in pretreatment and 10.18±1.95 million/ml in post treatment. The difference was not statistically significant (p>0.05). 63.9% oligospermic male showed improvement in sperm count in ebastin group and 18.1% in placebo group. Conclusions: Sperm count had significantly improved after three months’ treatment period with ebastin than placebo. Therefore, this study suggested that mast cell blocker ebastine can be helpful than placebo to improve the patients’ sperm count with oligospermia.